Interactional Styles Used by Christopher Gardner in Movie the Pursuit of Happyness - Daniel Nathan; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
The study "Interactional Styles Used by Christopher Gardner in Movie The Pursuit of Happyness" examines the different communication styles exhibited by the character Christopher Gardner in various situations. Using Holmes's (2006) theory of interactional styles, the study identifies both feminine and masculine features in Gardner's interactions. These features include facilitative, supportive feedback, indirect, person/process-oriented, and affectively oriented (feminine), as well as competitive, aggressive interruptions, direct, task/outcome-oriented, and referentially oriented (masculine).